Transcatheter aortic valve implantation using the left transcarotid approach in patients with previous ipsilateral carotid endarterectomy. Issue 7 (27th December 2014) - Pozzi, Matteo; Grinberg, Daniel; Obadia, Jean‐François; Saroul, Christine; Green, Lisa; Dementhon, Julie; Pizzighini, Sarah; Rioufol, Gilles; Finet, Gerard; Modine, Thomas
<x xml:space="preserve">Abstract</x> Objectives To assess the feasibility and safety of transcatheter aortic valve implantation (TAVI) through a left transcarotid approach in patients previously operated on for ipsilateral carotid endarterectomy (CEA). Background The healthcare impact of extracranial carotid artery disease is essential as stroke is the third‐leading cause of death in industrialized nations and CEA is often present in the history of patients awaiting TAVI. Methods The primary endpoint was to evaluate 30‐day mortality and freedom from major TAVI‐related complications in an observational analysis. Results From December 2011 to February 2014, we performed 9 TAVI. The mean age was 84.6 years. The procedure was performed without any technical complication or vascular injury in every patient. There was neither intraoperative mortality nor intraoperative major complications. One (11.1%) patient experienced spatial‐temporal disorientation but cerebral computed tomography did not show any sign of stroke. Two (22.2%) patients needed the implantation of a pacemaker due to third‐degree atrioventricular block appearance. Three (33.3%) patients were transfused with packed red blood cells and 1 (11.1%) patient developed a groin hematoma. Only 1 (11.1%) patient showed a residual paravalvular regurgitation ≥ 2. At 30‐day follow‐up there was neither mortality nor other TAVI‐related complications and echocardiography parameters remained stable. Conclusions TAVI through a left transcarotid approach in patients previously operated on for ipsilateral CEA is feasible and safe. The presence of a previous ipsilateral CEA represents no more a limitation to the utilization of this promising access route. At short‐term follow‐up, mortality and major complications rates are low. © 2014 Wiley Periodicals, Inc.